Composition of Non-Microbially Reducible Fe(III) in Aquatic Sediments - Phillips, Elizabeth J. P. (1993)
The production of small quantities of Fe(II) during the initial phase of microbial Fe(III) reduction greatly increased the amount of Fe(III) that could be extracted from freshwater sediments with oxalate. This finding and other evidence suggest that the oxalate-extractable Fe(III) that is unavailable for microbial reduction in anoxic sediments is not in the form of mixed Fe(III)-Fe(II) forms, as was previously suggested, but rather is in the form of highly crystalline Fe(III) oxides.